Cameron Turner on the Sound of Data (Audio Book) - Bruner, Jon; Cranor, David (O'Reilly Media, Inc., 2016)
How can sound be used to both generate data and express data? In this episode of the Hardware podcast, Jon Bruner and David Cranor talk with Cameron Turner, co-founder and principal at The Data Guild. Turner is the author of the new O'Reilly report "Finding Profit in Your Organization's Data: Examples and Best Practices."